UPAYA MENINGKATKAN PERHATIAN BELAJAR MELALUI MEDIA GAMBAR DENGAN MODEL PEMBELAJARAN DIRECT INSTRUCTION PADA SISWA KELAS II UPT SD NEGERI 11 PASUI - Ummu Khaltsum; Maulidya Apriana; Rahmawati. A; Fitriah Cahyani, Suci; Ismail (ASIAN PUBLISHER, 2022)
Efforts to Increase Learning Attention Through Media Pictures With Direct Instruction Learning Models in Grade II Students. This study aims to increase students' learning attention by using a learning model direct intruction. This type of research is classroom action research. This classroom action research uses a cycle model of planning, action, observation, and reflection. The subjects of this study were class II UPT SD Negeri 11 Pasui students. The number of students in the class were 13 students who consists of 3 male students and 10 female students. The results of the study show that the results of the evaluation of improvements in learning Indonesian appear to be quite good. Mastery of learning material increased from an average of 70 in the initial data, to 78 in the first cycle. Meanwhile, the level of learning completeness increased from only 36% in the initial data to 60% in the first cycle, there was an increase of 30% in the first cycle. cycle II there has been another increase to 81. Thus it can be seen that from the initial conditions to cycle I there has been an increase in grades meaning there has been an increase in learning. Then when viewed from cycle I to cycle II there is also an increase in the average value and the lowest score obtained by students. The results of this study can be concluded that using media images with the Direct Instruction learning model can increase students' attention in the learning process.